Studies on certain attributes of buffalo follicular fluid - DAS, G K; AGARWAL, S K; PATHAK, M K; SINGH, S K; SHANKER, UMA (The Indian Journal of Animal Reproduction, 2005)
The aim of the present investigation was to determine average yield of follicular fluid, total protein, estradiol and progesterone profile in the follicular fluid of buffalo ovaries. The follicular fluid was collected by aspirating the visible surface follicles. The average yield of buffalo follicular fluid (buFF) per ovary was 0.45±0.03 ml which was higher during the months between November to March (0.54±0.02 ml) than April to September (0.38±0.02 ml). The mean concentration of total protein in pooled buFF samples was 4.86±0.41 g% (ranged between 3.0 to 6.7 g%). The mean concentration of estradiol and progesterone in pooled buFF samples were 3044.99±31.85 pg/ml and 74.31±2.94 ng/rnl, respectively.